Differentiation Strategies in Premium Pricing: A Study of The Exclusive Value Principle in The Malaysian Wedding Photography Service Industry - Lim, Fiona Fei Lee (2009)
Wedding photography in Malaysia is close to hyper-competition. The influx of newcomers force veteran photographers to aggressively differentiate themselves to maintain competitive advantage. Some photographers have successfully differentiated their services through a premium pricing approach, the focus of this paper. An extensive literature review defines premium pricing as “a function of a firm’s extent to differentiate and its overall relative cost position compared to competitors provided it exceeds the cost of differentiation” Porter (1985). The Exclusive Value Principle introduced by Goth (1995), further indicates that customer’s perceived value of premium services is comprised of its quality and exclusivity attributes that resides in the utility and psychic domain respectively. Through use of the Differentiation Premium Model (Arnold, Hoffman and McCormick, 1989), the testability factor in services was found to be most significant for the industry in question. A survey was carried out to explore the factors influencing both the utility and psychic domains. Data collected indicates that within the premium segment, there are varying amounts of premiums that customers are willing to pay for and the factors that influence each premium bracket differ. Research findings suggest that the low and medium premium brackets (the largest groups) were willing to pay up to 100% premium and their main influencing factor was the tangible aspects of photography services. The high-end premium brackets who were willing to pay above 100% premium were motivated by the exclusivity factor while those who were willing to pay over 200% premium were not only motivated by the tangible aspects of the service but prioritized service customization and innovation, strategies that emphasized on satisfying customer needs. Through analyses of the survey data, it is shown that the main drivers for successful premium pricing strategies are quality and exclusivity. Be it celebrity status, or a unique service, it is the customers’ perception of value that allows the photographer to charge higher prices. The success enjoyed by local premium photographers such as Kid Chan (Kid Chan Studios), Zung (The Photoz) and Jim Liaw is proof of this.